Otolaryngological foreign bodies in a tertiary medical center in Turkey: A comparison of pediatric and adult patients (Annals of Medical Research, 2021)
Aim: The aim of the present research was to report on the characteristics of ear, nose, and throat foreign bodies in patients admitted to a tertiary medical center in Turkey and to analyze the extraction procedure, results, and complications.Material and Methods: A retrospective study conducted between August 2015 and May 2019 included 1042 patients referred to the emergency and otolaryngology department with ear, nose, and throat foreign bodies. The pediatric group included 612 cases, while the adult group included 430 cases. Sex, the type of foreign bodies, symptoms, extraction method, and complications were analyzed.Results: The most common foreign bodies were hard round objects frequently found in front of the middle turbine in the nose of children, while pieces of cotton buds were found in the outer ear canal in adults. In the pediatric group, the distribution of foreign bodies was 53.43% in boys and 46.57% in girls. Furthermore, the intervention was performed in three children (0.49%) admitted to the emergency department because of the organic foreign body escaping to the throat, as a result of which foreign bodies were removed. However, the prognosis for these patients was poor: a neurological sequela in one patient, death in two patients. In the adult group, the distribution of foreign bodies was 49.76% in males and 50.24% in females. No fatal cases were observed in this group. The ratio of foreign bodies removed under general anesthesia in the pediatric group was 3.43%, while it was 0.23% in the adult group, and the difference between them was statistically significant (p = 0.018). No statistical difference was observed between the groups with regard to complication rates (p>0.05). Conclusion: Otolaryngological foreign bodies are usually harmless, but they can cause infections and minor complications when they are overlooked or there is prolonged exposure, and these objects in the throat may be fatal, especially in children.
Keywords: Otolaryngology; foreign bodies; child; adult.